Tumor sizing technology: investigating current methods and possible technological improvements - Jaques, Jackson, author (Colorado State University. Libraries, 2024)
The precise measurement of tumors is critical for cancer diagnosis, staging, and treatment. With rapidly advancing imaging technology, the manual techniques of measuring and estimating tumors have evolved to digitally allow doctors to perform accurate measurements of the size of a tumor efficiently and reliably. Nevertheless, imaging technology has yet to keep pace with advances in tumor visualization tools that could improve the precision of clinical measurements. Such developments in tumor sizing technology will be addressed in this review, taking in current imaging modalities such as CT, MRI, PET, and emerging computational technologies, including those based on 3D modeling, virtual reality, and artificial intelligence. By evaluating them in conjunction, this review hopes to illustrate the pathway to improved staging, enhanced treatment planning, and ultimately more effective outcomes through technological advancements.
Colorado State University, College of Veterinary Medicine and Biomedical Sciences.
Keywords: tumor sizing; RECIST; cancer staging; virtual reality; advanced imaging technology; tumor visualization tools; 3D tumor modeling